The effect of students' effort–reward imbalance on learning engagement: the mediating role of learned helplessness and the moderating role of social support - Liu, Shengmin; Wang, Yuanru; He, Wanning; Chen, Yu; Wang, Qiangqiang (Frontiers in Psychology, 2024)
To explore the predictive effect of effort-reward imbalance on students' learning engagement and to elucidate the underlying mechanism, 796 students were selected for a survey.The students were required to complete the Effort-reward Imbalance Scale, the Learning Engagement Scale, the Learned Helplessness Questionnaire and the Perceived Social Support Scale. The results revealed that (1) the effort-reward imbalance of students significantly negatively predicts their learning engagement; (2) learned helplessness mediates the relationship between students' effort-reward imbalance and learning engagement; and (3) social support moderates the relationship between effort-reward imbalance and learned helplessness. High levels of social support can buffer the impact of an effort-reward imbalance on learned helplessness, and the protective effect of social support is more obvious when the effort-reward imbalance is low.The present study revealed how an effort-reward imbalance affects learning engagement among students through the dimensions of learned helplessness and perceived social support. The model constructed in this study not only further explains the mechanism underlying the relationship between effort-reward imbalance and learning engagement but also has certain guiding significance for students' education.